Transformasi Pada Era Disrupsi Hingga Terjadinya Revolusi Industri 4.0 - Riska Intan Pramitaning Tyas; Muhammad Yasin (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
Revolution means a process of change that takes place quickly or a fairly fundamental change in a field or place. If so, then the Industrial Revolution is a process of change that takes place quickly and fundamentally in the industrial sector. In modern civilization there have been four Industrial Revolutions, each of which has its own characteristics. The role of humans is gradually starting to be taken over by automatic machines. In short, disruption is innovation. This is innovation that will replace all old systems with new methods. Disruption has the potential to replace old players with new ones. Disruption replaces old, all-physical technology with digital technology that produces something completely new and more efficient and more useful.